Integrating Environmental Character Education and Eco-Enzyme Innovation for Community-Based Waste Management - Huda, Nurul; Adawiyah, Robiatul; Budiman, Budiman (Universitas Ahmad Dahlan, 2025)
Background: Household organic waste in Indonesia, which accounts for over 40% of total solid waste, creates major environmental, economic, and health challenges, especially in semi-urban areas with limited waste management systems and low community participation. This study explores the potential of eco-enzymes as a community-based innovation to reduce organic waste while promoting ecological literacy and environmental citizenship. Methods: A qualitative case study was conducted in Lebak Regency (September 2024–January 2025) involving households, schools, women’s groups, youth organizations, farmers, and the local environmental agency. Data were collected through observation, interviews, focus group discussions, and document analysis, and were analysed thematically following the Miles and Huberman framework. Results: The findings show that eco-enzyme training led to high adoption among participants, resulting in a noticeable reduction of household organic waste and methane emissions, while also strengthening community networks. Schools demonstrated higher levels of participation compared to households, indicating a gap between institutional practices and daily behaviour. Contribution: This study contributes an integrative and replicable model that combines technical innovation with community empowerment. Conclusion: Eco-enzyme interventions enhanced ecological literacy, encouraged pro-environmental behaviour, and supported local socio-economic activities, aligning with SDG 11.6 and 12.3. These findings highlight the importance of cross-sector collaboration linking schools, households, and communities for sustainable waste management.